2015
DOI: 10.1371/journal.pone.0124739
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Perfusion, Extent, Depth, Infection and Sensation (PEDIS) Classification System and Score in Patients with Diabetic Foot Ulcer

Abstract: AimsTo validate the perfusion, extent, depth, infection and sensation (PEDIS) classification system and to make the clinical practice easier, we created a score system and compared this system with two previously published common score systems.MethodsA retrospective cohort study was conducted on patients with diabetic foot ulcer (DFU) attending our hospital (n=364) from May 2007 to September 2013. Participants’ characteristics and all variables composing the PEDIS classification system were assessed.ResultsDur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 23 publications
2
108
0
10
Order By: Relevance
“…In addition, identifying patients with chronic wounds who meet inclusion criteria requires careful selection, with random sequence bias witnessed in studies using baseline as a control. Further, the Wagner classification scale chosen by the studies to categorise diabetic foot ulcers has been shown to be less reliable then other classification methods . For the studies featuring different chronic wounds, no classification scales for wound healing/severity were used by the authors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, identifying patients with chronic wounds who meet inclusion criteria requires careful selection, with random sequence bias witnessed in studies using baseline as a control. Further, the Wagner classification scale chosen by the studies to categorise diabetic foot ulcers has been shown to be less reliable then other classification methods . For the studies featuring different chronic wounds, no classification scales for wound healing/severity were used by the authors.…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines suggest that the depth of the wound is an important parameter of the prognosis . In the PEDIS classification system, wound depth is categorised as skin intact, superficial, fascia–muscle–tendon and bone–joint.…”
Section: Discussionmentioning
confidence: 99%
“…It does not include patient factors (end‐stage renal disease) or either the location or the number of foot ulcers. PEDIS has been validated in two studies for both wound healing and a composite endpoint of nonhealing, amputation, and death . It has also been demonstrated to have good reliability .…”
Section: Recommendations and Rationalementioning
confidence: 99%